2021
DOI: 10.1111/febs.15834
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell transcriptome profiling reveals molecular heterogeneity in human umbilical cord tissue and culture‐expanded mesenchymal stem cells

Abstract: Human umbilical cord‐derived mesenchymal stem/stromal cells (UMSCs) demonstrate great therapeutic potential in regenerative medicine. The use of UMSCs for clinical applications requires high quantity and good quality of cells usually by in vitro expansion. However, the heterogeneity and the characteristics of cultured UMSCs and the cognate human umbilical cord tissue at single‐cell resolution remain poorly defined. In this study, we created a single‐cell transcriptome profile of human umbilical cord tissue and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…The cells were then partitioned into gel beads in emulsion in the GemCode instrument, followed by reverse transcription, cDNA amplification, shearing, and adaptor-sample index attachment. Then, the 10X Genomics libraries were further prepared for the DNBSEQ platform as previously reported ( Wang et al, 2021 ). Briefly, the single-cell libraries were amplified using 10 cycles of polymerase chain reaction (PCR) and circularized by incubating with splint oligo (BGI) and T4 DNA ligase (BGI), followed by fragment size selection with PEG32 (BGI), rolling circle amplification (RCA), and sequenced using 100 bp paired-end on the DNBSEQ platform.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cells were then partitioned into gel beads in emulsion in the GemCode instrument, followed by reverse transcription, cDNA amplification, shearing, and adaptor-sample index attachment. Then, the 10X Genomics libraries were further prepared for the DNBSEQ platform as previously reported ( Wang et al, 2021 ). Briefly, the single-cell libraries were amplified using 10 cycles of polymerase chain reaction (PCR) and circularized by incubating with splint oligo (BGI) and T4 DNA ligase (BGI), followed by fragment size selection with PEG32 (BGI), rolling circle amplification (RCA), and sequenced using 100 bp paired-end on the DNBSEQ platform.…”
Section: Methodsmentioning
confidence: 99%
“…It is reported that heterogeneity of gene expression and distinct subpopulations exist in human primary Wharton’s jelly–derived MSCs by scRNA-seq ( Sun et al, 2020 ). Moreover, our previous study reveals molecular heterogeneity in human umbilical cord tissue and culture-expanded MSCs using scRNA-seq ( Wang et al, 2021 ). However, unlike the bone marrow-, adipose-, and umbilical cord-derived MSCs ( Liu et al, 2019 ; Sun et al, 2020 ; Wang et al, 2021 ), our knowledge about the heterogeneity of PMSCs at the single-cell level is still limited, especially the intersection between transcriptome and chromatin accessibility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In brief, because only individual c has the corresponding mother blood whole genome sequence variants, this sample was used as our training sample, for which each cell’s fetal or maternal origin was determined by demuxlet 53 using Cell Ranger-aligned BAM file from FS, Mid_S and Mat_S and WGS VCF file. And then, a fetal SNP dataset reference was built based on the corresponding umbilical single cell RNA sequencing data for each section from our previous study 54 . Using the difference ratio between a single cell SNP and the corresponding fetal SNP dataset reference, we calculated the Ratio of Mahalanobis distance of fetal cells and maternal cells usingthe following formulas:…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, the hypoxic culture environment has shown beneficial effects on preserving the stemness properties of MSCs and their multilineage differentiation capacity [ 35 , 51 , 52 , 53 , 54 , 55 ]. Interestingly, a molecular heterogeneity has been demonstrated between cell profiles of MSCs in vitro and in vivo [ 56 ]. A single-cell RNA sequencing analysis found that genes related to telomere length maintenance, including NHP2, CCT6A, RUVBL1 and APEX1, were highly expressed in culture-expanded human umbilical cord MSCs.…”
Section: Changes Induced In Mscs During In Vitro Expansionmentioning
confidence: 99%